2011
DOI: 10.1142/s1088424611004282
|View full text |Cite
|
Sign up to set email alerts
|

Indium as a central metal enhances the photosensitizing efficacy of benzoporphyrin derivatives

Abstract: Compared to benzoporphyrin derivative-dimethyl ester (BPD-DME) and its 8-(1′-hexyloxy)ethyl analog the corresponding In(III) complexes showed enhanced in vitro photosensitizing efficacy in Colon26 tumor cells, which could be due to their higher singlet oxygen producing ability. In both organic (methanol) and aqueous Bovine Calf Serum (17% BCS) solutions the metalated analogs were significantly more stable than the parent photosensitizers. Presence of Indium as a central metal gave 13–25 nm hypsochromic shift t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…The tumor-selective effects of the PDT are based on the preferential uptake and retention of the photosensitizer in the tumor [ 42 ]. The intracellular uptake and accumulation of photosensitizers has been a major problem in PDT especially when treating large solid tumors [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-selective effects of the PDT are based on the preferential uptake and retention of the photosensitizer in the tumor [ 42 ]. The intracellular uptake and accumulation of photosensitizers has been a major problem in PDT especially when treating large solid tumors [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Attachment of a linker bridging a fluorophore to a vitamin folic acid was shown by other groups to enhance aqueous solubility and selectivity when tested in folate-receptor enriched human nasopharyngeal epidermoid carcinoma KB cells [32]. Previous studies also demonstrated that zinc [30,33,34,35,36] and indium [31,37,38] metal coordination to chlorins enhances in vitro oxidative cell damage and higher singlet oxygen production, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Porphyrazine co‐ordination with Zn(II), Co(II), Ni(II), Pd(II), Gd(III), Mg(II) and Cu(II) has also been detailed . Conversely, research associating metal ions to the large class of chlorin‐based Ps for PDT are not common with the few reported studies including benzoporphyrins complexed to In(III), Pd(II) and Pt(II), bacteriochlorins complexed to Cu(II), Zn(II), Pd(II), NI(II), Cd(II), In(III) and Sn(II) and porphycenes complexed to Al(III) and Co(II) …”
Section: Shortcomings Of Current Photosensitizers For Phototherapymentioning
confidence: 99%
“…Associating physiochemical and photophysical traits of the resulting Ps, whether newly created or modified from a parental macrocycle, is then required to be documented. These include physical structure and conformation, molecular weight, ionic charge, axial and equatorial ligand interaction tendencies, metal‐based and ligand‐based redox coupling, UV–vis spectral profile, Ps*(S 1 ) lifetime, ISC potential (low for PDD and high for PDT applications), Ps*(T 1 ) lifetime and quantum yield and O 2 − yield Solubility enhancement or solutions: These studies deal with taking either a novel Ps of potential therapeutic application or those unable for use due to solubility issues and either modifying them for increased environmental interaction or interaction with various natural or synthetic drug delivery systems.…”
Section: Concluding Considerations For Researchmentioning
confidence: 99%
See 1 more Smart Citation